Oxidative status and serum leptin levels in obese prepubertal children - Ustundag, Bilal; Gungor, Serdal; Ayguen, A. Denizmen; Turgut, Mehmet; Yimaz, Erdal (Wiley, 2007)
The prevalence of obesity in children has increased dramatically over the last 20-30 years in developed countries. The aim of this study was to evaluate the oxidative and antioxidant status and any correlation with leptin in obese prepubertal children. A cross-sectional study was made of healthy children from ten elementary schools in the province of Elazig, Eastern Turkey. Blood samples were drawn from children comprising obese and control groups, on a visit to their school in the morning after an overnight fast. The mean body mass index (BMI) was 24.03+/-4.09 kg/m(2) in the obese group and was 17.51+/-2.33 kg/m(2) in the control group. Mean plasma leptin concentration was significantly higher in the obese children. Homocysteine and malondialdehyde (MDA) levels were also significantly higher in the obese group. In contrast superoxide dismutase (SOD) and glutathione peroxidase activities were significantly decreased in the obese group (p < 0.001). In conclusion, in prepubertal obese children oxidative stress was increased and MDA and homocysteine levels were well correlated with serum leptin level and BMI. In contrast with the increase in oxidative stress, antioxidant activities of SOD and glutathione peroxidase were decreased in obese prepubertal children. Copyright (c) 2006 John Wiley & Sons, Ltd.
Keywords: obesity; prepubertal children; leptin; glutathione peroxidase; superoxide dismutase; malondialdehyde; homocysteine